Exercise and autism: exploring caregiver insights on exercise participation and sleep patterns in autistic children in Aotearoa New Zealand - Bruce, Olivia; Sajjadi, Sayedeh Fatemeh; Galland, Barbara; Gross, Julien; Dainty, Gloria (Frontiers in Sleep, 2023)
Introduction: Autistic children experience sleep disturbances at a higher rate than do neurotypical children. It has been argued that sleep disturbances negatively impact behaviour, exacerbate learning difficulties, and decrease the quality of life among autistic children. Increasing exercise has been proposed to address sleep disturbances, however, little is known about how exercise might best be promoted for autistic children in Aotearoa New Zealand. Here, we explored caregivers’ lived experiences of their autistic child’s sleep disturbances and participation in exercise. Methods: Semi-structured interviews were conducted with 15 mothers of autistic children aged between 5 and 10. Mothers also completed the Sleep Disturbances Scale for Children (SDSC). Results: Scores on the SDSC indicated that there was considerable variation in sleep disturbance severity. Eight themes were identified from the interviews: sleep disturbances, the impact of exercise on sleep, exercise activities, whānau involvement in exercise, barriers for participation in exercise, support for participation in exercise, sensory considerations for participation in exercise, and activities specifically for children with special needs. Conclusions: Our findings highlight how challenging sleep disturbances can be for autistic children and their families and how participation in exercise can be promoted to potentially minimize their negative impact.